Infusion parameters, safety, and practical guidance for the manual administration of subcutaneous immunoglobulin 20% (Ig20Gly) - Grosse-Kreul, Dorothea; Allen, Crystal; Kalicinsky, Chrystyna; Keith, Paul K. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Primary immunodeficiency diseases (PIDs), also referred to as inborn errors of immunity, constitute a group of genetic conditions that affect the immune system. The current standard of care for patients with PIDs is lifelong immunoglobulin replacement therapy, delivered by intravenous (IVIG) or subcutaneous (SCIG) infusion. Immune globulin subcutaneous (human) 20% solution stabilized with glycine (Ig20Gly) is indicated as a replacement therapy for PIDs in adults and children of any age in Europe and in patients aged 2 years and above in the USA. Typically, Ig20Gly is administered using an infusion pump; however, delivery of Ig20Gly by manual administration has recently been approved in Europe. Practical recommendations on the use of Ig20Gly manual administration are lacking; this review therefore aims to provide guidance for use of this method of administration. Additionally, we summarize the infusion parameters, safety, patient-reported outcomes, and economic benefits associated with Ig20Gly manual administration. Manual administration of Ig20Gly was shown to permit faster rates of infusion than administration via infusion pump. Patients typically infused at two or fewer infusion sites with manual administration of Ig20Gly. Safety and tolerability profiles were similar for Ig20Gly manual administration and administration by infusion pump. Overall, there were comparable levels of patient satisfaction with manual administration and infusion pump, with patient preference deemed to be a key determinator of success for either method of administration. Economic studies identified cost savings for the healthcare system through manual administration compared with IVIG or SCIG infusion by infusion pump because of the reduced equipment costs and nurse support. For infusion of Ig20Gly by manual administration, a syringe and butterfly needle are used; patients are advised to start infusion at 1–2 mL/min to prevent discomfort. Overall, manual administration of Ig20Gly offers an effective and well-tolerated alternative to administration by infusion pump.